Long-term application of glycine transporter inhibitors acts antineuropathic and modulates spinal N-methyl-D-aspartate receptor subunit NR-1 expression in rats - Barthel, Franziska; Urban, Andrea; Schlösser, Lukas; Eulenburg, Volker; Werdehausen, Robert; Brandenburger, Timo; Aragon, Carmen; Bauer, Inge; Hermanns, Henning (Anesthesiology, 2014)
Dysfunction of spinal glycinergic neurotransmission is a major pathogenetic factor in neuropathic pain. The synaptic glycine concentration is controlled by the two glycine transporters (GlyT) 1 and 2. GlyT inhibitors act antinociceptive in various animal pain models when applied as bolus. Yet, in some studies, severe neuromotor side effects were reported. The aim of the current study was to elucidate whether continuous inhibition of GlyT ameliorates neuropathic pain without side effects and whether protein expression of GlyT1, GlyT2, or N-methyl-D-aspartate receptor subunit NR-1 in the spinal cord is affected.In the chronic constriction injury model of neuropathic pain, male Wistar rats received specific GlyT1 and GlyT2 inhibitors (ALX5407 and ALX1393; Sigma-Aldrich, St. Louis, MO) or vehicle for 14 days via subcutaneous osmotic infusion pumps (n = 6). Mechanical allodynia and thermal hyperalgesia were assessed before, after chronic constriction injury, and every 2 days during substance application. At the end of behavioral assessment, the expression of GlyT1, GlyT2, and NR-1 in the spinal cord was determined by Western blot analysis.Both ALX5407 and ALX1393 ameliorated thermal hyperalgesia and mechanical allodynia in a time- and dose-dependent manner. Respiratory or neuromotor side effects were not observed. NR-1 expression in the ipsilateral spinal cord was significantly reduced by ALX5407, but not by ALX1393. The expression of GlyT1 and GlyT2 remained unchanged.Continuous systemic inhibition of GlyT significantly ameliorates neuropathic pain in rats. Thus, GlyT represent promising targets in pain research. Modulation of N-methyl-D-aspartate receptor expression might represent a novel mechanism for the antinociceptive action of GyT1 inhibitors.
EVALuna2:4702